The history of the present English subjunctive a corpus-based study of mood and modality - Moessner, Lilo (Edinburgh University Press, 2020)
Locating the subjunctive at the interface of mood and modality, this book presents a systematic description of the use of the English subjunctive in main clauses, noun clauses, relative clauses, and adverbial clauses in the Old English, Middle English and Early Modern English periods.